2013
DOI: 10.1039/c3dt50567g
|View full text |Cite
|
Sign up to set email alerts
|

Carbon quantum dots enhance the photocatalytic performance of BiVO4 with different exposed facets

Abstract: Carbon quantum dots (CQDs) were demonstrated to have the ability to enhance the photocatalytic performance of monoclinic BiVO4 with different exposed facets under visible light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(79 citation statements)
references
References 30 publications
(33 reference statements)
5
73
0
1
Order By: Relevance
“…The CDs/NiFe-LDH complex exhibits high electrocatalytic activity (with overpotential *235 mV in 1 M KOH at a current density of 10 mA cm −2 ) and stability for oxygen evolution. This almost exceeded those of any previous Ni-Fe compounds and even was comparable to that of the lowest overpotential reported in Ni-Fe catalysts, ∼230 mV at 10 mA cm −2 for electrodeposited Ni-Fe films [169,207,217]. Typically, nickel acetate and iron nitrate (with a molar ratio of Ni/Fe = 5) were hydrolyzed in a mixed N,N-dimethylformamide (DMF) and CDs aqueous solution at 85°C for 4 h. Followed by redispersing the intermediate product in a DMF/H 2 O mixed solvent and through a solvothermal treatment at 120°C for 12 h, then a second solvothermal step at 160°C for 2 h. The solvothermal treatment may lead to the crystallization of NiFe-LDH nanoplates and formation of the nanocomposites.…”
Section: Cds/nife Layered Double Hydroxide Compositesupporting
confidence: 67%
“…The CDs/NiFe-LDH complex exhibits high electrocatalytic activity (with overpotential *235 mV in 1 M KOH at a current density of 10 mA cm −2 ) and stability for oxygen evolution. This almost exceeded those of any previous Ni-Fe compounds and even was comparable to that of the lowest overpotential reported in Ni-Fe catalysts, ∼230 mV at 10 mA cm −2 for electrodeposited Ni-Fe films [169,207,217]. Typically, nickel acetate and iron nitrate (with a molar ratio of Ni/Fe = 5) were hydrolyzed in a mixed N,N-dimethylformamide (DMF) and CDs aqueous solution at 85°C for 4 h. Followed by redispersing the intermediate product in a DMF/H 2 O mixed solvent and through a solvothermal treatment at 120°C for 12 h, then a second solvothermal step at 160°C for 2 h. The solvothermal treatment may lead to the crystallization of NiFe-LDH nanoplates and formation of the nanocomposites.…”
Section: Cds/nife Layered Double Hydroxide Compositesupporting
confidence: 67%
“…27,28 Recently, the photocatalytic enhancement of semiconductor based (i.e. TiO2) materials impregnated with a visible active polymer, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…3b). In the light of the present literatures, those m-BiVO 4 products with preferred orientation growth of (0 1 0) facets possess this kind of sheet-like morphology [28,29]. The BiVO 4 sample synthesized with 25% glycerol aqueous solution (Fig.…”
Section: Morphology Characterizationmentioning
confidence: 98%
“…It has been reported that the surface structure of photocatalysts plays an important role to their photocatalytic activities because the photocatalytic reaction or photoelectron conversion takes place only when photogenerated electrons and holes are available on the surface [21][22][23][24]. Many semiconductor photocatalysts have active facets for photocatalysis, for example, the (0 0 1) facets of anatase TiO 2 are much more reactive than the thermodynamically stable (1 0 1) facets [25][26][27][28]. For m-BiVO 4 , research interest has already started in tuning its crystal facets for optimizing the photocatalytic reactivity.…”
Section: Introductionmentioning
confidence: 99%